Effects of carbonated drink as an extender on semen characteristics, fertility and hatchability in Nigerian Indigenous Chicken - Adebisi, Adeyina Oluwatoba (Journal of Agricultural Sciences (Belgrade), 2021)
Abstract Commercial carbonated drink (CD) as an extender was evaluated on semen characteristics, fertility and hatchability in Nigerian indigenous chicken (NIC). Under the condition of 370Celsius, 5% and 10% of CD were added to egg yolk citrate solution to make 100%. NIC cock semen were added to the extenders and preserved for 0, 30 and 60 minutes respectively in a factorial design layout. Percentage motility of sperm cells was significantly (p<0.05) higher in 5% CD inclusion compared with 10% CD inclusion and control. Motility decreased with increase in preservation time across the treatments. Fertility and hatchability of eggs were also significantly (p<0.05) higher in 5% CD inclusion. It was concluded that carbonated drinks at 5% inclusion in an extender can preserve cock sperm cells for 60 minutes with improvement in fertility and hatchability of eggs.